DETERMINAN KEPATUHAN WAJIB PAJAK BADAN INDUSTRI MANUFAKTUR (Studi Kasus di KPP Pratama Demak) - Desy Nurkhasanah, 11.05.62.0003; Hardiningsih, Pancawati (Students Journal of Accounting and Banking, 2014)
This study aims to examine and analyze the effect of perceived behavioral control, financialcondition, the condition of its facilities and the organization climatic conditions on tax compliance body.The population in this study is the Corporate Taxpayers manufacturing industry in the territory ofDemak STO. Sample selection method used was convinience sampling / based coincidence. The dataanalysis technique used is multiple linear regression analysis.Based on the results of tests performed can be seen that the perception of behavioral control,financial condition, the condition of its facilities and the organization climatic conditions and asignificant positive effect on tax compliance entities, either partially or simultaneously.Keywords: perceived behavioral control, financial condition, the condition of its facilities, theorganization climatic conditions and compliance corporate taxpayers